Schoolcraft's expedition to lake itasca : the discovery of the source of the Mississippi - Schoolcraft, Henry Rowe, 1793-1864 (Michigan State University Press, 1993)
Scientist, explorer, historian, and Indian agent Henry Rowe Schoolcraft's name must be included in the pantheon of early nineteenth-century adventurers who were in the vanguard of American expansion into the heart of the continent. While some, individuals like William Clark, Meriwether Lewis, John C. Fremont, and Kit Carson did not stop until they reached the Pacific Ocean, others took it as their task to explore the cast, unknown interior; chief among this group was Henry Rowe Schoolcraft. Originally issued by Michigan State University Press in 1958, Schoolcraft's Expedition to.